The role of forensic audit science in corruption case handling of equipment procurement of driving license simulator (sim) - Gressi Hariyanti (Universitas Mercu Buana Yogyakarta, 2016)
This study aimed is finding out if the new science of accounting role in handling corruption cases plaguing Indonesia. There are two suspects in this case are Djoko Susilo and Didik Purnomo. The data collecting was done through electronic media, mass media and website. This research is a form of case studies which has the main question ifthere is any role of forensic audit science in corruption case handling of equipment procurement of driving license simulator (SIM)or not. The analysis shows that the science of forensic audit is able to assist the government in dealing with cases of corruption in Indonesia.